Metabolomics of the effects of Yishenjiangya granules in older adults with hypertension - Ma, Yongbo; Liu, Yingying; Zhuang, Li; Dai, Xia; Yao, Li; Yu, Jie; Zhang, Lei (Frontiers in Pharmacology, 2025)
IntroductionOlder adults are a high-risk group for hypertension, with specific characteristics regarding symptoms and treatment. Yishenjiangya granules (YJG), a traditional Chinese medicinal decoction, are widely used to reduce blood pressure and improve clinical symptoms. This study aimed to use metabolomics to explore the clinical effects and underlying mechanisms of YJG in hypertension in older adults.MethodsThe study enrolled patients aged ≥65 years, with systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg in sitting positions on different days; the control group comprised 30 healthy participants with normal blood pressure and biochemistry indicators. Ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) was used to analyze plasma metabolites in patients with hypertension before and after YJG intervention.ResultsAfter YJG treatment, blood pressure decreased significantly; some metabolites showed a trend approaching the control group. UPLC-Q-TOF-MS analysis identified 30 YJG-targeted plasma metabolites in older adult patients with hypertension, including three major metabolic pathways: linoleic acid, arachidonic acid, and glycerophospholipid metabolism.ConclusionThis study identified that metabolite changes may underlie the clinical mechanism of YJG in treating older adult patients with hypertension, providing a basis for further treatment of hypertension.